2013
DOI: 10.1371/journal.pone.0081909
|View full text |Cite
|
Sign up to set email alerts
|

Limited Internal Radiation Exposure Associated with Resettlements to a Radiation-Contaminated Homeland after the Fukushima Daiichi Nuclear Disaster

Abstract: Resettlement to their radiation-contaminated hometown could be an option for people displaced at the time of a nuclear disaster; however, little information is available on the safety implications of these resettlement programs. Kawauchi village, located 12–30 km southwest of the Fukushima Daiichi nuclear power plant, was one of the 11 municipalities where mandatory evacuation was ordered by the central government. This village was also the first municipality to organize the return of the villagers. To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
6
32
0
1
Order By: Relevance
“…Following Japan's Fukushima Daiichi Nuclear Power Plant incident, triggered by the Great East Japan Earthquake and subsequent tsunami on 11 March 2011, 1 health threats have arisen in the radiationcontaminated areas, and cumulative dose from external and internal radiation exposure is the major public concern. 1-5 Contrary to the concern, as Tsubokura et al and Hayano et al [6][7][8][9][10][11][12][13][14][15] acknowledged in their continuing series of studies and assessments of levels of radiation exposure due to the Fukushima incident, the levels of dose attributed to the incident have been low owing to the weathering process and the success of contaminated food control. The United Nations Scientific Committee on the Effects of Atomic Radiation and the WHO have concluded that the predicted risk of lifetime cancer is very low in the general public, except for the most exposed infants and children in the Fukushima Prefecture, in whom thyroid cancer cases exceeding the norm are estimated by model calculations, although they are difficult to verify in practice due to the low normal rates of thyroid cancer, even a large relative increase represents a small absolute increase in cases.…”
Section: Introductionmentioning
confidence: 99%
“…Following Japan's Fukushima Daiichi Nuclear Power Plant incident, triggered by the Great East Japan Earthquake and subsequent tsunami on 11 March 2011, 1 health threats have arisen in the radiationcontaminated areas, and cumulative dose from external and internal radiation exposure is the major public concern. 1-5 Contrary to the concern, as Tsubokura et al and Hayano et al [6][7][8][9][10][11][12][13][14][15] acknowledged in their continuing series of studies and assessments of levels of radiation exposure due to the Fukushima incident, the levels of dose attributed to the incident have been low owing to the weathering process and the success of contaminated food control. The United Nations Scientific Committee on the Effects of Atomic Radiation and the WHO have concluded that the predicted risk of lifetime cancer is very low in the general public, except for the most exposed infants and children in the Fukushima Prefecture, in whom thyroid cancer cases exceeding the norm are estimated by model calculations, although they are difficult to verify in practice due to the low normal rates of thyroid cancer, even a large relative increase represents a small absolute increase in cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the data accumulated and disseminated so far have consistently shown that the internal contamination for the majority of residents has fortunately been so low as to be undetectable [2]. These data include, for example, whole-body-counter surveys [3][4][5][6], duplicatediet studies [7], and the inspection of "all rice in all rice bags" harvested in Fukushima (2012-2014) [8].…”
Section: Introductionmentioning
confidence: 99%
“…A nuclear disaster can cause various health problems including leukaemia2 and thyroid cancer3 among children. A recent study suggests that a nuclear disaster might worsen chronic diseases such as diabetes mellitus or hyperlipidaemia as a result of adopting an inactive, indoor lifestyle in an attempt to reduce outdoor radiation exposures 4. In addition, it may cause mental problems such as post-traumatic stress disorder in addition to physical problems 5.…”
Section: Case Presentationmentioning
confidence: 99%